Management of Raudloh Tarbiyyatil Qur’an (RTQ): Islamic Activities for Elementary School Students’ Self Development - Al Afgani, Yaomi; Ariyani, Dewi (Proceeding of Saizu International Conference on Transdisciplinary Religious Studies, 2023)
This study is based on students’ inability to apply Islamic teachings. The purpose of this research is to examine the management of Raudloh Tarbiyyatil Qur’an (RTQ), a self-development program in Islamic studies at MI Ma’arif NU 1 Pageraji Banyumas Indonesia. This study employs a qualitative approach with a case study methodology. The study lasted from April 4th, 2023 to June 4th, 2023. The data was gethered through observation, interviews, and documentation. Data were analyzed using steps such as data reduction, data display, and conclusion drawing. According to the findings of this study, the Raudloh Tarbiyyatil Qur’an program has the following management functions: 1) Planning by setting goals, developing strategies for the creation of a goal including teaching and education personnel, activities to be carried out, determining learning methods, and preparing learning plans; 2) Organization by preparing the organizational structure, authority and responsibility, placement of human resources; 3) Implementing Raudloh Tarbiyyatil Qur’an by implementing planned activities and programs, and evaluating the results of program activities, which in Raudloh Tarbiyyatil Qur’an include three things, namely: tahfiz, reading and writing the Qur'an, and ubudiyyah. All of these activities are carried out on a scheduled basis and are included in the self-development stage and the learning stage; 4) Supervision oversees the process of implementing teacher performance activities.